Materiais à base de óxido de ferro para oxidação de compostos presentes no efluente da despolpa do café Oxidation of organic compounds in wastewater from the humid processing of coffee berries - Maraísa Gonçalves; Mário César Guerreiro; Luiz Carlos Alves Oliveira; Cristian Luciana da Rocha (Química Nova, 2008)
Materials based on pure iron oxide and impregnated with niobia (Nb2O5) were prepared. Their catalytic activities were tested on the oxidation of compounds present in the wastewater from the processing of coffee berries. Particularly caffeine and catechol were tested. The oxidation reactions were carried out with the following systems (i) UV/H2O2, (ii) photo-Fenton and (iii) heterogeneous Fenton. All materials were characterized with X-ray diffraction, Mössbauer and infrared spectroscopy. Iron was mainly in the forms of goethite and maghemite. The oxidation kinetics were monitored by UV-vis and the oxidation products were monitored by mass spectrometry. The photo-Fenton reaction presented highest oxidation efficiency, removing 98% of all caffeine and catechol contents.